2017
DOI: 10.1002/ejoc.201700581
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Amido Esters and Amido Phosphonates through Carbonylation of Diazo Compounds Followed by Nucleophilic Addition Reaction

Abstract: We report a method to produce amido esters and amido phosphonates. Octacarbonyldicobalt [Co2(CO)8] was found to be an efficient nongaseous CO source that could be used as a reagent for the carbonylation of diazo esters and diazo phosphonates under mild reaction conditions. A number of diazo esters and diazo phosphonates smoothly underwent the reaction with CO, which was generated from Co2(CO)8, to produce the corresponding ketenes. The subsequent reaction with an amine afforded the expected amido esters and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
(83 reference statements)
1
12
0
Order By: Relevance
“… 30 , 31 , 35 Indeed, cobalt has recently been proved to be a practical metal to perform a vast array of transformations. Particularly, the use of carbene precursors has attracted recent interest due to their versatility as coupling partners in transformations such as carbonylation 36 , 37 and annulation, 38 44 including Co( iii )-radical-based outer-sphere functionalization ( Scheme 1a ). Regarding C–H functionalization, the field was pioneered by Miura using Co( ii ) salts.…”
Section: Introductionmentioning
confidence: 99%
“… 30 , 31 , 35 Indeed, cobalt has recently been proved to be a practical metal to perform a vast array of transformations. Particularly, the use of carbene precursors has attracted recent interest due to their versatility as coupling partners in transformations such as carbonylation 36 , 37 and annulation, 38 44 including Co( iii )-radical-based outer-sphere functionalization ( Scheme 1a ). Regarding C–H functionalization, the field was pioneered by Miura using Co( ii ) salts.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, so far, Davies report of carbene insertion into the ‐OH bond of p‐tosyl sulfonic acid is the only known example in the literature for functionalization of the −OH bond of sulfonic acid. In this regard and in continuation of our research on carbene insertion reactions [67–72,81,83,86‐87] we herein report the insertion of carbene into the O−H bond of aromatic sulfonic acids using α‐diazo ester to generate the sulfonic esters.…”
Section: Introductionmentioning
confidence: 79%
“…insertion, cross coupling, cyclopropanation, cycloaddition and rearrangement [64–66] . In light of this, the carbene insertion into the X−H bonds has been utilized for the synthesis of α –amino, α –hydroxyl, α ‐silyl, or α –acyloxy ester derivatives [67–72] . Owing to its broad range of applicability and high reactivity, vanadyl bisacetylacetonate [VO(acac) 2 ] has proven to be a valuable catalyst in a wide range of organic transformations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently our research group reported the synthesis of amido esters and amido phosphonates by efficiently utilizing the ketene generated from the reaction of carbene from the diazo compounds and metal carbonyls . In continuation of this, herein we have report the synthesis of diesters by the carbonylation of carbene generated from phenyldiazoesters followed by nucleophilic addition of alcohol to the ketene.…”
Section: Introductionmentioning
confidence: 99%